2013
DOI: 10.1093/europace/eut333
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation patients do not benefit from acetylsalicylic acid

Abstract: Acetylsalicylic acid as monotherapy in stroke prevention of atrial fibrillation has no discernable protective effect against stroke, and may even increase the risk of ischaemic stroke in elderly patients. Thus, our data support the new European guidelines recommendation that ASA as monotherapy should not be used as stroke prevention in atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 18 publications
1
50
1
5
Order By: Relevance
“…However, the inferior effectiveness of antiplatelets for stroke prophylaxis in atrial fibrillation has been clearly demonstrated, 29 and this is not compensated for by a greater safety, 29,30 especially compared with the novel single-target oral anticoagulants. 31 Therefore, the widespread belief that antiplatelets provide adequate protection with a lower incidence of adverse effects is not justified, and antiplatelet therapy is currently not considered a valid stroke prophylaxis therapy in high-risk patients with atrial fibrillation, except if the patient rejects anticoagulation after detailed information.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inferior effectiveness of antiplatelets for stroke prophylaxis in atrial fibrillation has been clearly demonstrated, 29 and this is not compensated for by a greater safety, 29,30 especially compared with the novel single-target oral anticoagulants. 31 Therefore, the widespread belief that antiplatelets provide adequate protection with a lower incidence of adverse effects is not justified, and antiplatelet therapy is currently not considered a valid stroke prophylaxis therapy in high-risk patients with atrial fibrillation, except if the patient rejects anticoagulation after detailed information.…”
Section: Discussionmentioning
confidence: 99%
“…Dowody przemawiające za monoterapią lekiem przeciwpłytkowym w celu zapobiegania udarom mózgu w AF są bardzo ograniczone [38,[428][429][430]. Leczenie za pomocą VKA zapobiega udarom mózgu, zatorowości w krążeniu systemowym, zawałom serca i zgonom z przyczyn naczyniowych lepiej niż pojedyncze lub podwójne leczenie przeciwpłytkowe ASA i klopidogrelem (roczne ryzyko 5,6% podczas stosowania ASA i klopidogrelu vs. 3,9% podczas stosowania VKA) [431].…”
Section: Leczenie Przeciwpłytkowe Jako Postępowanie Alternatywne W Stunclassified
“…This has resulted in undertreatment or in the inappropriate substitution of other antithrombotic agents, such as aspirin. Contrary to popular opinion, aspirin has not significantly lowered the risk of stroke from AF in any single randomized trial 5,33 and is especially inferior to OAC therapy in the elderly population, where aspirin is often used. 32,34 However, since approximately 2010, several novel OACs (NOACs) have become available, including the direct thrombin inhibitor dabigatran 35 and the factor Xa inhibitors rivaroxaban, apixaban, and edoxaban.…”
Section: Special Reportmentioning
confidence: 72%